(untitled) (Journal of Environmental Bioremediation and Toxicology, 2023)
Water is becoming the most limiting factor for sustainable crop production. The application of superabsorbent polymer SAP hydrogel as a soil conditioner can improve soil natural environments, water retention and release capacity, nutrient use efficiencies and agricultural produce. This study aimed to determine the efficiency of different superabsorbent polymer rates on soybean growth performance. The superabsorbent polymer used in this study, 0 (Control), 5 g, 10 g and 15 g were mixed thoroughly with the loamy soil and used to fill the 10×10cm poly bags. The experiment was laid out in a Randomized Complete Block Design (RCBD) involving two soybean varieties: TGX- 1951-3F and TGX-448-2E, with four treatments and three replications. The results of this study indicate that, application of 5 g, 10 g and 15 g of super absorbent polymer resulted an increase in plant height, number of leaves, number of branches, stem girth, leaf area, and plant biomass studied as compared to the control 0 g which recorded lower mean performance. Similarly, it was evident from this study that the performance of the traits studied increased with an increase in the number of weeks after plant germination. This increase proves that SAP can improve crop cultivation, especially with pronounced climate change.